2001
DOI: 10.5014/ajot.55.1.55
|View full text |Cite
|
Sign up to set email alerts
|

The Movement Assessment Battery for Children: A Comparison of 4-Year-Old to 6-Year-Old Children From Hong Kong and the United States

Abstract: These findings highlight the need to ensure that norms for all tests are appropriate for the specific cultural groups being assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
4
30

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 15 publications
6
77
4
30
Order By: Relevance
“…What is even more worrying about the low average score of participants is that the BOT-2 BF motor proficiency assessment tool is designed to assess motor deficiencies and therefore consists of basic tasks. These findings coincide with previous research findings worldwide that typically demonstrate average or Running Head: Motor proficiency of children in the UK 11 below average motor proficiency in children Booth, 2004 andSigmunson &Rostoft, 2003), with few exceptions (Chow et al, 2001). …”
Section: Discussionsupporting
confidence: 82%
“…What is even more worrying about the low average score of participants is that the BOT-2 BF motor proficiency assessment tool is designed to assess motor deficiencies and therefore consists of basic tasks. These findings coincide with previous research findings worldwide that typically demonstrate average or Running Head: Motor proficiency of children in the UK 11 below average motor proficiency in children Booth, 2004 andSigmunson &Rostoft, 2003), with few exceptions (Chow et al, 2001). …”
Section: Discussionsupporting
confidence: 82%
“…For example the Movement ABC norms and individual test items compared across cultures showed that North American norms are appropriate in Europe (Smits-Engelsman, Henderson, & Michels, 1998) but not so well suited to Asian populations (Chow, Henderson, & Barnett, 2001;Miyahara et al, 1998). Finally, individuals from different countries and cultural backgrounds may use different strategies to perform test items.…”
Section: Introductionmentioning
confidence: 99%
“…To start with, significant differences favoring girls were found in studies providing a total battery score (Charlop & Atwell, 1980;Sigmundsson & Rostoft, 2003) and a composite battery score (Sigmundsson & Rostoft, 2003;Silva & Ross, 1980), and in skills like hopping (Castetbon & Andreyeva, 2012;du Toit & Pienaar, 2002), skipping (Ulrich & Ulrich, 1985), posting coins (Chow et al, 2006), threading beads, drawing trail (Chow, Henderson, & Barnett, 2001;Chow et al, 2006;Sigmundsson & Rostoft, 2003), or tasks involving balance (Castetbon & Andreyeva, 2012;Fjørtoft, 2000;Lam, Ip, Lui, & Koong, 2003;Lejarraga et al, 2002;Morris, Williams, Atwater, & Wilmore, 1982) and flexibility (Bala, 2003; Table 1).…”
Section: Research-article2016mentioning
confidence: 99%